Pengaruh Pertumbuhan Ekonomi dan Kemiskinan Terhadap Alokasi Apbd Provinsi Aceh Tahun Anggaran 2015-2018 - Rahmah Yulianti; Khairuna Khairuna (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
The objective of this study is to examine the influence of economic growth, poverty on the allocation of the Aceh Provincial Budget for the 2015-2018 period. Economic growth is measured by GDP, poverty is measured by the poverty line (GK), and the APBD allocation is measured by the realization of regional income, expenditure and regional financing. The population in this study are data and information regarding the APBD allocation, the economic sector PDRB and the Poverty Line. This study uses APBD allocation data, economic growth data and poverty data which is seen from the survey conducted by BPS 2015-2018 period, and uses census method. To test the hypothesis, this study uses multiple linear regression analysis. Results show that, (1) economic growth and poverty simultanly, have influence to APBD allocation, (2) economic growth have positive influence to APBD allocation, (3) poverty have negative influence to APBD allocation.